2019
DOI: 10.1136/bmjopen-2019-032498
|View full text |Cite|
|
Sign up to set email alerts
|

Transcultural mediation programme in a paediatric hospital in France: qualitative and quantitative study of participants’ experience and impact on hospital costs

Abstract: ObjectiveIn France, immigrants with chronic diseases encounter numerous difficulties in gaining access to care and then in its initiation and organisation, difficulties only partly explained by socioeconomic factors. A transcultural mediation consultation programme has been set up in Necker Hospital in Paris to help families and professionals deal with these situations. The objective of this study was to assess the economic impact and the experience of this consultation.DesignQualitative and quantitative descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We further identified 127 records through grey literature searches, and after deduplication and removal of records published before 2019, we retrieved and assessed 59 full‐text reports for eligibility (Figure 1). A total of 63 reports were included in this review, representing 61 unique interventions 41–103 . Furthermore, we consulted additional publications, which were cited in the eligible reports, for additional details about 23 of the 61 included interventions during our data charting 104–132 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We further identified 127 records through grey literature searches, and after deduplication and removal of records published before 2019, we retrieved and assessed 59 full‐text reports for eligibility (Figure 1). A total of 63 reports were included in this review, representing 61 unique interventions 41–103 . Furthermore, we consulted additional publications, which were cited in the eligible reports, for additional details about 23 of the 61 included interventions during our data charting 104–132 …”
Section: Resultsmentioning
confidence: 99%
“…Communication and information provision 45 [41][42][43][44][45][49][50][51][52][53][54][56][57][58]60,61,63,64,66,67,[73][74][75][76][77][78]80,82,[84][85][86][87][88][89][90][91][92][93][94][96][97][98][99][100][101][102][103] In-person interactions with providers 27 [42][43][44][45][51]…”
Section: Approaches Number Of Interventions Implementation Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the request of one of the health professionals involved in the patient's care, a transcultural mediator, teamed with a cultural broker from the same ethnocultural background as the patient, sees the patient, his or her family, and the medical team for a single two-hour consultation aimed at improving the team's interactions with the patient and family. The objective of the transcultural mediation consultation is to modify the conditions of the interaction between the medical teams, on the one hand, and between patients and their families on the other (Bouznah, 2020; Lachal et al, 2019). The shared narrative of cultural and medical representations may allow each to find meaning in what goes on in treatment and to understand that the different concepts and discourses about the disease can coexist, that is, that one does not necessarily exclude the other.…”
Section: Introductionmentioning
confidence: 99%
“…A 2016 evaluation of this service in a children's hospital found that it: i) cut health-care costs, by reducing emergency department visits, ii) improved the patient–physician relationship and helped them to understand one another, and iii) significantly enhanced trust between doctors and patients. The doctors reported, in particular, that this trust was owed in part to their increased confidence in the families’ ability to manage the disease by better adherence to the treatment (Lachal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%